Test–Retest Reliability of Self-Reported Sexual Behavior History in Urbanized Nigerian Women - Dareng, Eileen O.; Adebamowo, Sally N.; Eseyin, Olabimpe R.; Odutola, Michael K.; Pharoah, Paul P.; Adebamowo, Clement A. (Frontiers in Public Health, 2017)
Background: Studies assessing risk of sexual behaviour and disease are often plagued by questions about the reliability of self-reported sexual behaviour. In this study, we evaluated the reliability of self-reported sexual history among urbanized women in a prospective study of cervical HPV infections in Nigeria. Methods: We examined test-retest reliability of sexual practices using questionnaires administered at study entry and at follow up visits. We used the root mean squared approach to calculate within-person coefficient of variation (CVw) and calculated the intra-class correlation coefficient (ICC) using a two way, mixed effects models for continuous variables and κ statistics for discrete variables. To evaluate the potential predictors of reliability, we used linear regression and log binomial regression models for the continuos and categorical variables respectively. Results: We found that self-reported sexual history was generally reliable, with overall ICC ranging from 0.7 to 0.9, however the reliability varied by nature of sexual behaviour evaluated. Frequency reports of non-vaginal sex (agreement = 63.9%, 95% CI: 47.5% - 77.6%) were more reliable than those of vaginal sex (agreement = 59.1%, 95% CI: 55.2% - 62.8%). Reports of time-invariant behaviours were also more reliable than frequency reports. The CVw for age at sexual debut was 10.7 (95% CI: 10.6 – 10.7) compared with the CVw for lifetime number of vaginal sex partners which was 35.2 (95% CI: 35.1 – 35.3). The test-retest interval was an important predictor of reliability of responses, with longer intervals resulting in increased inconsistency (Average change in unreliability for each one month increase = 0.04, 95% CI = 0.07 – 0.38, p = 0.005). Conclusion: Our findings suggest that overall, the self-reported sexual history among urbanized Nigeran women is reliable.